1994
DOI: 10.1017/s1074070800026389
|View full text |Cite
|
Sign up to set email alerts
|

A Logit Analysis of Participation in Tennessee's Forest Stewardship Program

Abstract: This study determines the likely effect of cost-share incentives on participation in the Tennessee forest Stewardship Program and identifies other factors that may contribute to participation. A random utility model is used to determine the probability that a landowner will choose to participate in the program. A binary choice model is specified to represent the dichotomous decision and a logit procedure is used to fit the model. Data are obtained from mail surveys of 4,000 randomly selected landowners. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 5 publications
3
36
0
1
Order By: Relevance
“…Previous studies have emphasized the strong predictive power of farmer's values and attitudes (e.g., Lynne et al, 1988;Bell et al, 1994;Vanslembrouck et al, 2002;van Putten et al, 2011;Luzar and Diagne, 1999;Defrancesco et al, 2008) and the reason for holding land (Pannell et al, 2006). Attachment to the land (Ryan et al, 2003) as well as the importance of owner's objectives associated with farming or owning land per se (Emtage and Herbohn, 2012;de Young, 2000).…”
Section: Lessons Learned Regarding the Profile Of Adoptersmentioning
confidence: 99%
“…Previous studies have emphasized the strong predictive power of farmer's values and attitudes (e.g., Lynne et al, 1988;Bell et al, 1994;Vanslembrouck et al, 2002;van Putten et al, 2011;Luzar and Diagne, 1999;Defrancesco et al, 2008) and the reason for holding land (Pannell et al, 2006). Attachment to the land (Ryan et al, 2003) as well as the importance of owner's objectives associated with farming or owning land per se (Emtage and Herbohn, 2012;de Young, 2000).…”
Section: Lessons Learned Regarding the Profile Of Adoptersmentioning
confidence: 99%
“…Their participation in the programs prompted the owners to spend an average of $2767 of their own funds for forest management activities, with nearly two-thirds saying they would not done have made the expenditure if they had not received a cost-share [320]. Other researchers identified factors that affected participation in conservation programs [321][322][323][324]. Two related NIPF studies noted that broad-based conservation programs and their multiple resource objectives requirement were well-received by forest owners.…”
Section: Integrated Federal Natural Resource Cost-sharing Programsmentioning
confidence: 99%
“…Much of the research that identified specific management practices on family forests tied these practices to federal or state forestry incentive programs, and thus stresses reforestation and timber stand improvement type activities [280][281][282][283][284][285][286][287][288][289][290][291][292][293][294][319][320][321][322][323][324]335,418]. Many of these practices undertaken on family forests, however, are related not to timber production, but to wildlife habitat management, recreation, scenic values, and wetlands [319,324,356,358].…”
Section: Private Forest Management Planning and Practicesmentioning
confidence: 99%
“…The literature relates to choice behavior regarding technology, foods, and services, and choice models have been utilized to predict human decision-making behavior in these studies. Examples include decision-making relating to chemical-free foods (Baker 1999;Magnusson and Cranfield 2005), organic foods (Loureiro et al 2001), environmental services (Bell et al 1994), technology (Moon and Balasubramanian 2004;Adesina and Zinnah 1993), and farm diversification (Windle and Rolfe 2005).…”
Section: Empirical Analysismentioning
confidence: 99%